Sociolinguistic styles - Hernández Campoy, Juan Manuel, (Language in society (Oxford, England), 2016)
"Sociolinguistic Styles systematically examines the complex phenomenon of style-shifting in sociolinguistics, focusing on its nature and social motivations, as well as on the mechanisms for its usage and its effects"--